Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan terhadap Tax Avoidance pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2017-2020 - William Immanuel Hitijahubessy; Sulistiyowati Sulistiyowati; Devvy Rusli (Jurnal Ekonomi, 2022)
This study aims to determine whether the effect of Profitability, Leverage, and Company Size on Tax Avoidance in manufacturing companies for the 2017-2020 period listed on the Indonesia Stock Exchange. This study uses a quantitative research method using panel data regression as measured by Eviews version 10. The sample was determined based on the purposive sampling method, with a total sample of 64 manufacturing companies so that the total observations in this study were 256 observations. The data used in this study is secondary data in the form of financial reports obtained from the official IDX website: www.idx.co.id and related company websites. Hypothesis testing using t test. The results of the study prove that, (1) profitability has a negative effect on tax avoidance, (2) leverage has a negative effect on tax avoidance, (3) firm size has a positive effect on tax avoidance.